Comparative Analysis of the Nutrient and Anti-Nutrient Compositions of Five Different African Eggplants. - Akin-Osanaiye, Bukola Catherine; Hassan, Aisha; Abodunde, Clement Abiodun (Food, Agriculture and Natural Resources - NETWORKS, 2024)
Five distinct African eggplants were used in the study to determine their nutritional and anti-nutrient contents which include: Solanum aethiopica, Solanum gilo, Solanum inacnum, Solanum macrocarpon and Solanum melomgena. These analyses were carried using standard methods. The result indicated that S. inacnum has the highest proximate composition with calorific value of 306.45 kcal, S. gilo recorded the lowest carbohydrate value (9.28%). S. aethiopica, had the lowest proximate values but recorded the most value of crude fibre (22.00 ± 0.02%). S. macrocarpon has a low crude protein of 10.47% and a higher carbohydrate of 40.74 while S. melomgena has the highest carbohydrate and moisture of 42.98 and 84.58% respectively. There is no significant difference (p≤0.5) between the values obtained for all the minerals, in all the eggplants. The anti-nutrient analysis showed that S. gilo has the highest oxalate (6.01 ± 0.02mg/g). S. macrocarpon has a lower saponin (14.05 ± 0.02), hydrocyanic acid (4.34 ± 0.02) and phenol (1.45 ± 0.0l). S. melongena has the lowest tannin of 1.01 ± 0.01 but has the highest nitrate of 1.03 ± 0.01 µg/g. This shows that the eggplant, S. incanum, has the highest nutrient composition and can be eaten regularly for health benefits.